KONVERSI KEAGAMAAN PASCA 1965, MENGURAI DAMPAK SOSIAL BUDAYA DAN HUBUNGAN ISLAM KRISTEN DI PEDESAAN JAWA - M. Alie Humaedi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
The relationship between Islam and Christianity in various regions is often confronted with situations caused by external factors. They no longer debate the theological aspect, but are based on the political economy and social culture aspects. In the Dieng village, the economic resources are mostly dominated by Christians as early Christianized product as the process of Kiai Sadrach's chronicle. Economic mastery was not originally as the main trigger of the conflict. However, as the political map post 1965, in which many Muslims affiliated to the Indonesian Communist Party convert to Christianity, the relationship between Islam and Christianity is heating up. The question of the dominance of political economic resources of Christians is questionable. This research to explore the socio cultural and religious impact of the conversion of PKI to Christian in rural Dieng and Slamet Pekalongan and Banjarnegara. This qualitative research data was extracted by in-depth interviews, observations and supported by data from Dutch archives, National Archives and Christian Synod of Salatiga. Research has found the conversion of the PKI to Christianity has sparked hostility and deepened the social relations of Muslims and Christians in Kasimpar, Petungkriono and Karangkobar. The culprit widened by involving the network of Wonopringgo Islamic Boarding. It is often seen that existing conflicts are no longer latent, but lead to a form of manifest conflict that decomposes in the practice of social life.